Association of polymorphisms in NR1I2 and ABCB1 genes with epilepsy treatment responses. (September 2007) - Hung, Chin-Chuan; Jen Tai, John; Kao, Pi-Ju; Lin, Min-Shung; Liou, Horng-Huei
Objectives: The aim of this study was to investigate whether the polymorphisms in the NR1I2 and ABCB1 genes were associated with epilepsy treatment responses.Methods & results: NR1I2 and ABCB1 polymorphisms were genotyped in 114  drug-resistant epileptic patients, 213 seizure-free patients and 287 normal controls. Highly specific real-time PCR was applied to detect the variants by using TaqMan allelic specific probe. For a single gene test, it was demonstrated that 3435C>T in the ABCB1 gene had a significant effect on epilepsy treatment responses, but polymorphisms in the NR1I2 gene did not. Further analysis using a logistic regression model revealed that only 2677G>T and 3435C>T in the ABCB1 gene and their interaction term were associated with drug-resistant epilepsy after adjustment for etiology and epilepsy classification. In the present study, the polymorphisms in the NR1I2 gene were not significantly associated with epilepsy treatment responses.Conclusion: Our results indicated that 2677G>T and 3435C  >  T in the ABCB1 gene contributed to drug-resistant epilepsy. Although biologically plausible, the polymorphisms in NR1I2 investigated in the present study did not play a role in epilepsy treatment responses. Other unveiled genetic variants in the NR1I2 gene that may have the potential to affect ABCB1 gene expression are worth further investigation in future studies.